Current tools to interrogate microglial biology - Dumas, Anaelle Aurelie; Borst, Katharina; Prinz, Marco (Neuron (Cambridge, Mass.), 2021)
Microglial cells perform a plethora of functions in the central nervous system (CNS), involving them in brain development, maintenance of homeostasis in adulthood, and CNS diseases. Significant technical advancements have prompted the development of novel systems adapted to analyze microglia with increasing specificity and intricacy. The advent of single-cell technologies combined with targeted mouse models has been decisive in deciphering microglia heterogeneity and dissecting microglial functions. However sophisticated these tools have become, clear limitations remain. Understanding their pitfalls and advantages ensures their correct application. Therefore, we provide a guide to the cutting-edge methods currently available to dissect microglial biology. Microglial cells perform a plethora of functions in the central nervous system (CNS), involving them in brain development, maintenance of homeostasis in adulthood, and CNS diseases. Significant technical advancements have prompted the development of novel systems adapted to analyze microglia with increasing specificity and intricacy. The advent of single-cell technologies combined with targeted mouse models has been decisive in deciphering microglia heterogeneity and dissecting microglial functions. However sophisticated these tools have become, clear limitations remain. Understanding their pitfalls and advantages ensures their correct application. Therefore, we provide a guide to the cutting-edge methods currently available to dissect microglial biology.